(untitled) (Mustansiria Dental Journal, 2018)
High stresses which result during functions in the cast clasps arms are the main causes of deformations or fractures. The purpose of the study was to evaluate the stress distribution in three-dimensional finite element analysis models of clasps and to select their preferable design. A three-dimensional finite element analysis was used for the investigations. Preformed clasp wax patterns for circumferential clasps were selected and three parameters namely length, thickness and width at the base and tip were measured to generate purposely designed experimental three-dimensional models. Generated stresses and deformatioans were calculated numerically and plotted graphically. Within the limitations of this study, the preferable cross-sectional shape of the retentive cast circumferential clasp arm was determined as half-round and the taper 0.6 mm. the ideal cross section of the retentive clasp arm was half round with 0.6mm taper diameter.